2020
DOI: 10.1007/s00420-020-01520-x
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and mental wellbeing after electrical accidents: a survey and a clinical study among Swedish male electricians

Abstract: Purpose The purpose was to examine long-term consequences of exposure to electrical current passing through the body. We investigated (1) whether electricians after having experienced an electrical accident report more cognitive problems and lower mental wellbeing and (2) have objectively verifiable reduced cognitive function; and (3) which circumstances at the time of the accident affect long-term subjective cognitive function and mental wellbeing? Methods A survey of male electricians who had experienced ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
(65 reference statements)
0
3
0
3
Order By: Relevance
“…En kartlegging vi har gjennomført ved St. Olavs hospital, peker i retning av at en stor andel av pasienter med strømgjennomgang fra lavspenning kan utredes og behandles poliklinisk, uten at pasientsikkerheten reduseres (10). På bakgrunn av tidligere anbefalinger, våre kliniske erfaringer samt nyere li eratur om risiko for sekvele e er lavspenningsulykker (11) presenterer vi et forslag til algoritme for aku håndtering av pasienter e er strømgjennomgang fra lavspenning (figur 1).…”
Section: «Anbefalinger Basert På Nyere Norske Erfaringer Og Som Tar H...unclassified
See 2 more Smart Citations
“…En kartlegging vi har gjennomført ved St. Olavs hospital, peker i retning av at en stor andel av pasienter med strømgjennomgang fra lavspenning kan utredes og behandles poliklinisk, uten at pasientsikkerheten reduseres (10). På bakgrunn av tidligere anbefalinger, våre kliniske erfaringer samt nyere li eratur om risiko for sekvele e er lavspenningsulykker (11) presenterer vi et forslag til algoritme for aku håndtering av pasienter e er strømgjennomgang fra lavspenning (figur 1).…”
Section: «Anbefalinger Basert På Nyere Norske Erfaringer Og Som Tar H...unclassified
“…Håndterte pasienter må få informasjon ved hjemreise om å ta kontakt med legevakt eller fastlege hvis de opplever hjertebank, brystsmerter, synkope, økende muskelsmerter, parestesier eller temperaturstigning (12). Siden seneffekter forekommer (1,11,20), bør pasientene oppfordres til å kontakte fastlege dersom de opplever vedvarende symptomer. De bør informeres om mulig utvikling av kroniske smerter, nummenhet og mental påvirkning, som bør følges opp av fastlege.…”
Section: Informasjon Til Pasienterunclassified
See 1 more Smart Citation
“…Besides the physiological damages, electrical injuries have been reported to cause psychological problems, such as post-traumatic stress disorder(PTSD) [ 4 7 ], depression [ 5 9 ], anxiety [ 6 8 , 10 , 11 ], sleep disorders [ 5 7 , 10 , 11 ], cognitive problems [ 6 , 8 , 11 , 12 ] and sexual dysfunction [ 9 , 11 ]. An American retrospective study evaluated psychiatric examinations of 73 referred electrical injured patients and found that having experienced “no-let-go” or having lost or impaired consciousness was associated with psychiatric diagnosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A larger multicenter study from Canada with 114 patients, who were interviewed shortly after the injury and again one year later, found that several neuropsychological complaints were persistent over time or even increased [ 17 ]. However, a recent Swedish study found no long-term cognitive dysfunctions [ 12 ].…”
Section: Introductionmentioning
confidence: 99%